DIE’l’ARY CHOLESTEROL REQUIREMENT OF LARVAE AND POSTLARVAE OF THE PRAWN PENAEUS INDICUS (H. MILNE EDWARDS) - PAULRAJ, R.; CHANDGE, M. S. (Journal of Indian Fisheries Association, 2015)
Two sets of experiments were conducted to determine the dietary cholesterol requirement of larvae and postlarvae 1 10 of Penaeus indicus. Seven approximately isocaloric and isonitrogenous purified experimental diets were tried with graded levels of cholesterol ranging from 0 to 4%. The control feed for larvae and postlarvae 1 10 were phytoplankton and compounded feed NPCLÂ·17, developed by CMFRI, Cochin respectively. Result of these experiments indicate that cholesterol is an essential Â·nutrient in the diet of larvae and postlarvae 1-10. Survival and growth of larvae and postlarvae 1-10 were greatly affected by cholesterol deficiency in the diet. The optimal cholesterol requirement for larvae appeared to be 0.5% of the diet, while it was higher for postlarvae where inclusion of cholesterol at a level of 2% in the diet gave higher growth.